Social isolation and feelings of loneliness among older people during pandemic covid-19: A conceptual review - Khairul Hanim Pazim; Roslinah Mahmud; Dayangku Aslinah Abd Rahim; Siti Hajar Samsu; Lim, Fui Yee Beatrice (Academic Inspired Network, 2022)
Several studies have found an increase in social isolation and feelings of loneliness since the outbreak of the COVID-19 pandemic, particularly among the elderly. Although oldage loneliness is important public health that has been a primary concern issue long before the outbreak, the government's social distancing and stay-at-home measures put in place worldwide to combat the spread of the disease have become a challenge that has intensified the feelings of loneliness. Social isolation and loneliness have dangerous consequences on mental health in older adults, especially for the group of the already vulnerable elderly. Understanding what causes social isolation and loneliness during a pandemic could help plan for future pandemic management since safety measures appear to have a negative impact on loneliness.